ANALISIS KINERJA KEUANGAN DAN HARGA SAHAM PERBANKAN DI BURSA EFEK INDONESIA (BEI) - - Wijayanti (Journal of Indonesian Applied Economics, 2010)
This  research was  aimed  at  searching  the  anwer  for question whether  financial achievement of firm really affected the price of its stock or the speculative activites were the main sources for stock price fluctuation. Financial performance was shown by  some  fundamental  indicators  such  as CAR, ROA, NIM, NPL, LDR,  EPS,  and PER, while speculation often look over the historical pattern of  stock prices in thepast which indicated by P1 and P2.   Regression was used as  the tools for analyzing the problem. Data were collected from all banks listed in BEJ in 2005. The research found that overall, all variables had significant impact on stock prices, but not all individual variable had  the same role. Variables: ROA, NIM, EPS, PER, and   P1 were individually had significant impact  on the stock price while CAR, NPL, LDR and P2  did  not.  Thus,    author  concluded  that  beside  financial  indicators  could influence people to buy and sell their stock, the stock price was also still significantly affected by the action of speculants.Keywords: financial achievement, speculation, banks, stock price.